Antigen distribution in mucocutaneous biopsies of human paracoccidiomycosis - Sandoval, Marina; Brito, T. de; Sotto, Mirian N.; Santos, R. T.; Franco, M. F. [UNESP] (My University, 1996)
The authors studied the distribution of Paracoccidioides brasiliensis antigen(s) in human skin and oral mucosa. In biopsies obtained from untreated patients showing the chronic form of the disease, the authors demonstrated the P. brasiliensis antigen using two polyclonal immune sera raised in rabbits, one against the exoantigens of P. brasiliensis and the other against a 43-kDa glycoprotein. Langerhans' cells were detected through double immunolabeling using an anti-S100 protein monoclonal antibody. Double labeling immunohistochemistry showed that both of the immune sera labeled the yeast cells in the center of the granuloma and those transmigrating through the epithelial layer equally well. Granulomas exhibited the P. brasiliensis antigen permeating cells, mainly at the periphery of the granulomatous inflammation. The P. brasiliensis antigen(s) accumulated in the macrophages but not in the Langerhans' cells. P. brasiliensis antigens, detected by antiserum against parasite exoantigens, were also deposited between basal keratinocytes, but not in the granular cells, in 47% of the biopsies. P. brasiliensis antigens, as assessed by immunoelectron microscopic techniques, are present in the cytoplasm of the yeast cells in the host tissues. Antigens are transported to the cell membrane and later excreted through the cell wall. Antigenic deposits are also seen at the fungus-host interface.
Keywords: Antigen(s); Immunohistochemistry; Paracoccidioides brasiliensis; Paracoccidioidomycosis; Skin and oral mucosa biopsies; Ultrastructural labeling; human; human tissue; immunoelectron microscopy; immunohistochemistry; major clinical study; oral biopsy; paracoccidioides brasiliensis; priority journal; skin biopsy; south american blastomycosis